Association between the Number of Unfamiliar Vegetables and Dietary Factors of Elementary School Children - Song, K.H., Myongji University, Gyeonggi , Republic of Korea; Lee, H.M., Daejin University, Gyeonggi, Republic of Korea (Preventive nutrition and food science, 2013)
Despite well established health benefits, today is children do not eat enough vegetables. The purpose of this study was to determine the association between the number of unfamiliar foods in the vegetable food group and the preference for these foods and dietary factors. Subjects were 1,072 children in 5th and 6th grades from elementary schools located in 4 cities in Gyeonggi-do, Korea. A two-page questionnaire consisted of questions asking about the subjects’ preference and familiarity for 64 foods in the vegetable group, preferences for three fast foods, four types of vegetable dishes, and six tastes. Also included in the questionnaire were questions assessing subjects’ adherence to national dietary guidelines. The subjects were divided into quintiles according to the number of unfamiliar vegetables; the 1st quintile (N=226) was children who had less than 14 unfamiliar vegetables and the 5th quintile (N=229) was more than 29. Compared to the children in the other quintiles, the children in the 5th quintile had a significantly lower adherence to national dietary guidelines regarding consumptions of vegetable and protein sources, regular exercise, awareness of desirable height and weight, and reading food labels, as well as total (P0.05). The preferences for bland tastes (P0.05), salads (saengchae, P0.01), stir-fried vegetables (P0.01), and several vegetable items (P0.05) were significantly lower in the 5th quintile compared to the other quintiles. This study proposes the potential benefits of teaching children names of a variety of vegetables to improve their dietary factors such as food preferences and dietary habits.